RESPONSIBLE GROWTH AND BUSINESS RESILIENCE IN MSMES: AN INTEGRATIVE FRAMEWORK FOR SUSTAINABLE ENTERPRISE DEVELOPMENT - Ricky Agusiady; Kosasih (Journal of Jabar Economic Society Networking Forum, 2024)
This conceptual paper develops an integrative framework for responsible growth in micro, small, and medium enterprises (MSMEs). The analysis connects the resource-based view, dynamic capabilities, absorptive capacity, organizational learning, social capital, open innovation, resilience, and entrepreneurial-ecosystem perspectives. It does not claim primary survey, interview, experimental, or statistical data. The synthesis argues that financial discipline, stakeholder value, adaptive capability, risk governance, and organizational learning should be organized as repeatable managerial routines rather than treated as isolated interventions. The framework proposes staged diagnosis, implementation, evaluation, and learning mechanisms and identifies implications for owner-managers, support organizations, and future empirical research.